2012
DOI: 10.1007/s00281-012-0337-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial regulation of allergic responses to food

Abstract: The incidence of food allergy in developed countries is rising at a rate that cannot be attributed to genetic variation alone. In this review we discuss the environmental factors that may contribute to the increasing prevalence of potentially fatal anaphylactic responses to food. Decreased exposure to enteric infections due to advances in vaccination and sanitation, along with the adoption of high-fat (Western) diets, antibiotic use, Caesarian birth, and formula feeding of infants, have all been implicated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 191 publications
(233 reference statements)
2
31
0
2
Order By: Relevance
“…Emerging studies emphasize the interaction of environmental factors, including diet, antibiotic usage and others, with components of the immune system, affecting their function and modify the outcome of the immune response 8 . They also support the idea that the commensal bacteria play a central role in the regulation of allergic diseases and that they dynamically interact with host genetic background and environmental factors to promote or disrupt oral tolerance 9-11 . Genetic and immunological evidence also reinforce the idea of a pivotal role for regulatory T (T Reg ) cells in promoting tolerance to allergens and preventing allergic disorder 12-16 .…”
Section: Introductionsupporting
confidence: 64%
“…Emerging studies emphasize the interaction of environmental factors, including diet, antibiotic usage and others, with components of the immune system, affecting their function and modify the outcome of the immune response 8 . They also support the idea that the commensal bacteria play a central role in the regulation of allergic diseases and that they dynamically interact with host genetic background and environmental factors to promote or disrupt oral tolerance 9-11 . Genetic and immunological evidence also reinforce the idea of a pivotal role for regulatory T (T Reg ) cells in promoting tolerance to allergens and preventing allergic disorder 12-16 .…”
Section: Introductionsupporting
confidence: 64%
“…The composition of the microbiota is dynamic and strongly influenced by the external environment. It can be dramatically altered by diet, antibiotic use, mode of birth, formula feeding, vaccination and exposure to pathogens (reviewed in [3]). It is now hypothesized that changes in the composition of the microbiota, called dysbiosis, lead to a loss of protective bacterial signals, which can cause both allergic and inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Rising disease prevalence over a short period cannot be explained by genetic variation alone, renewing interest in the role of the environment in shaping allergic sensitization to food (2,3). First proposed more than 20 years ago, the hygiene hypothesis suggested that societal efforts to reduce exposure to infectious microbes early in life have deprived the immune system of immunoregulatory stimulation necessary for protection against allergic disease (4).…”
mentioning
confidence: 99%